PENGARUH DIGITAL MARKETING, E - SERVICE QUALITY DAN E - TRUST TERHADAP KEPUTUSAN PEMBELIAN ONLINE PADA PENGGUNA E COMMERCE TOKOPEDIA DI FAKULTAS PSIKOLOGI UNIVERSITAS PRIMA INDONESIA - Wirda Anggraini; Sindi Fadila; Rosnelly Pakpahan; Jarungjung Hutagaol; Nirwana Br. Bangun (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This Research Was Conducted For Tokopedia E-Commerce Users Of The Psychology Department Of Prima Indonesia University. The Purpose Of This Research1 Was1 To Evaluate How Digital Marketing1 Influences Purchasing Decisions, To Examine How Purchasing Decisions Are Influenced By The Quality Of E-Services, And To Examine How E-Trust Influences Purchasing Decisions Marketing Influences Product Quality. The Influence1 Of E-Services And E-Trust On Online Purchasing Decisions Of Tokopedia E-Commerce Customers Faculty Of Psychology, Prima Indonesia University. The Sample Size Of This Quantitative Research Is 68 Students And The Total Population Is 217 Students. Data Were Collected Using Questionnaires And SPSS Version 23.0 Was Used For Data Analysis. As A Result, Among Tokopedia E- Commerce Users, Digital Marketing Affects Purchasing Decisions, Electronic Service Quality Affects Purchasing Decisions, Electronic Trust Affects Digital Marketing, And Purchasing Decisions, Electronic Service Quality, We Found That Electronic Trust Affects Online Purchasing Decisions. The Influence Of Psychology. Prima Indonesia University.